2018
DOI: 10.1002/mnfr.201700902
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Influences Pancreatic Islets by Opposing Effects on Electrical Activity and Insulin Release

Abstract: Resveratrol addresses multiple targets in pancreatic islets. Potentiation of insulin secretion is mediated by SIRT1-dependent activation of cAMP/EPAC1. Considering resveratrol as therapeutic supplement for patients with type 2 diabetes mellitus, the inhibitory influence on electrical excitability attenuates positive effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…In the following paragraphs, all of the selected nutraceuticals have a positive effect on insulin secretion or pancreatic protection, mainly including polyphenols (resveratrol, [6]-gingerol, and curcumin), flavonoids (genistein), polysaccharides (7WA and fucoidan), triterpenoid (oleanolic acid), and alkaloid (coixol) (Table 1). Previous studies have reported that resveratrol has the ability to reduce blood glucose and improve insulin sensitivity by preventing the degradation of cAMP [43,44]. Additionally, a recent study reported that daily orally administration of [6]-gingerol for 28 days for db/db mice significantly increases glucose-stimulated insulin secretion and enhances glucose tolerance.…”
Section: The Dietary Bioactive Ingredients Targeting Pancreas Camp Signaling For Glucose Homeostasismentioning
confidence: 99%
See 1 more Smart Citation
“…In the following paragraphs, all of the selected nutraceuticals have a positive effect on insulin secretion or pancreatic protection, mainly including polyphenols (resveratrol, [6]-gingerol, and curcumin), flavonoids (genistein), polysaccharides (7WA and fucoidan), triterpenoid (oleanolic acid), and alkaloid (coixol) (Table 1). Previous studies have reported that resveratrol has the ability to reduce blood glucose and improve insulin sensitivity by preventing the degradation of cAMP [43,44]. Additionally, a recent study reported that daily orally administration of [6]-gingerol for 28 days for db/db mice significantly increases glucose-stimulated insulin secretion and enhances glucose tolerance.…”
Section: The Dietary Bioactive Ingredients Targeting Pancreas Camp Signaling For Glucose Homeostasismentioning
confidence: 99%
“…Previous studies have reported that resveratrol has the ability to reduce blood glucose and improve insulin sensitivity by preventing the degradation of cAMP [ 43 , 44 ]. Additionally, a recent study reported that daily orally administration of [6]-gingerol for 28 days for db/db mice significantly increases glucose-stimulated insulin secretion and enhances glucose tolerance.…”
Section: Pancreasmentioning
confidence: 99%
“…Resveratrol (trans‐3,4,5‐trihydroxy‐stilbene; RE), a traditional Chinese medicine, is known as a naturally occurring compound with potent biological properties . It is found in plants, such as grapes, giant knotweed, peanuts and mulberries .…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, it has been reported that the multiple aspects of the action of RSV on the mechanisms control glucose homeostasis [61]. Polyphenol plays a protective role on pancreatic islets by increasing the synthesis of antioxidant enzymes, such as superoxide dismutase, glutathione peroxidase, and glutathione-s-transferase, which counteract the action of free radicals [62]. The antiapoptotic power toward β-cells has emerged both in animal models with streptozotocin toxic damage and in the autoimmune insulin of type 1 diabetes mellitus, where the action of RSV manifests itself by reducing the expression of the chemokine receptor 6 and inhibiting the migration of inflammatory cells into the pancreas [63,64].…”
Section: Diabetesmentioning
confidence: 99%